Kebijakan Dan Etika Dalam Penggunaan AI Pada Praktik Akuntansi - Hafizh Dzaky Hawari; Rizki Aryanto; Rifqi Muzakki (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
This research aims to investigate and identify the ethical importance of using AI in accounting practices, and see whether AI in accounting practices has an impact on overall business performance and to create guidelines to encourage accounting professionals to understand and adopt ethical practices. The narrative of this review is driven by the context depicted and the accounting practices found in the articles selected and used as a sample. This provides a strong basis for the argument that AI itself despite its enabling and mediating role in accounting cannot make ethical accounting decisions. Descriptive research methods with a systematic literature review (SLR) approach are used to explore how previous research results show artificial intelligence and accounting. The results of this research indicate that policies and ethics in the use of AI in accounting professional accounting practices can optimize the company's use of artificial intelligence. The availability of caseware-based audit software and cloud-based accounting software will reduce the demand for professional accounting services in the technology sector.